2010
DOI: 10.1111/j.1468-232x.2010.00604.x
|View full text |Cite
|
Sign up to set email alerts
|

Gender‐Compensation Differences Among High‐Level Executives in the United States

Abstract: Bertrand and Hallock (2001: 3) present compelling evidence that female executives in the United States earned 45 percent less total compensation than their male counterparts for 1992-1997. We complement their results by analyzing data over a longer time period and, more importantly, contend that most of the unexplained gender difference in total pay among executives was due to gender differences in the portion of variable pay, in particular a different cash payout from stock option exercises.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
53
0
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(57 citation statements)
references
References 53 publications
(68 reference statements)
3
53
0
1
Order By: Relevance
“…For example, the studies of Vieito and Khan (2012), Munoz-Bullon (2010), Bell (2005) and Bertrand and Hallock (2001) provide evidence that there is a gender difference in executive pay and that male executives are compensated at higher levels than female executives. Bell (2005) also documents that the gender pay gap for female executives reduces when a firm is led by a female CEO.…”
Section: Introductionmentioning
confidence: 96%
“…For example, the studies of Vieito and Khan (2012), Munoz-Bullon (2010), Bell (2005) and Bertrand and Hallock (2001) provide evidence that there is a gender difference in executive pay and that male executives are compensated at higher levels than female executives. Bell (2005) also documents that the gender pay gap for female executives reduces when a firm is led by a female CEO.…”
Section: Introductionmentioning
confidence: 96%
“…Therefore, an original offer may not be reflective of the agreed‐upon starting salary and thus may actually underestimate the pay gap. Additionally, research on the gender pay gap at the executive level has also indicated that most (90%) of the gap is attributed to variable pay (such as stock options) rather than base salary (Muñoz‐Bullón, ). Similar to our findings, this research found that executive base pay shows no significant gender gap when controlling for occupational and industry control variables (Muñoz‐Bullón, ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, research on the gender pay gap at the executive level has also indicated that most (90%) of the gap is attributed to variable pay (such as stock options) rather than base salary (Muñoz‐Bullón, ). Similar to our findings, this research found that executive base pay shows no significant gender gap when controlling for occupational and industry control variables (Muñoz‐Bullón, ). Therefore, our respondents’ starting salary figure may not have incorporated the largest facet of the gender pay gap at the executive level.…”
Section: Discussionmentioning
confidence: 99%
“…Estes resultados poderão indicar que embora o diferencial de género exista e seja elevado em Portugal, neste caso de 93,864% desfavorável às mulheres, no que toca aos salários, esta diferença não é estatisticamente significativa, contrariando, assim, outros estudos como o de Pichler et al (2008), Bowlin e Renner (2008), Munoz-Bullón (2010) ou Kulich et al (2011).…”
unclassified